De Novo ZMYND8 variants result in an autosomal dominant neurodevelopmental disorder with cardiac malformations - Dias, Kerith-Rae; Carlston, Colleen M.; Blok, Laura E. R.; De Hayr, Lachlan; Nawaz, Urwah; Evans, Carey-Anne; Bayrak-Toydemir, Pinar; Htun, Stephanie; Zhu, Ying; Ma, Alan; Lynch, Sally Ann; Moorwood, Catherine; et al. (Genetics in medicine, 2022)
Purpose - ZMYND8 encodes a multidomain protein that serves as a central interactive hub for coordinating critical roles in transcription regulation, chromatin remodeling, regulation of super-enhancers, DNA damage response and tumor suppression. We delineate a novel neurocognitive disorder caused by variants in the ZMYND8 gene. - Methods - An international collaboration, exome sequencing, molecular modeling, yeast two-hybrid assays, analysis of available transcriptomic data and a knockdown Drosophila model were used to characterize the ZMYND8 variants. - Results - ZMYND8 variants were identified in 11 unrelated individuals; 10 occurred de novo and one suspected de novo; 2 were truncating, 9 were missense, of which one was recurrent. The disorder is characterized by intellectual disability with variable cardiovascular, ophthalmologic and minor skeletal anomalies. Missense variants in the PWWP domain of ZMYND8 abolish the interaction with Drebrin and missense variants in the MYND domain disrupt the interaction with GATAD2A. ZMYND8 is broadly expressed across cell types in all brain regions and shows highest expression in the early stages of brain development. Neuronal knockdown of the Drosophila ZMYND8 ortholog results in decreased habituation learning, consistent with a role in cognitive function. - Conclusion - We present genomic and functional evidence for disruption of ZMYND8 as a novel etiology of syndromic intellectual disability.